Economic Analysis of On-Grid Solar Power Plant System Design in The Building Of Politics,Law And Human Rights Ministry At North Penajam Paser Regency,East Kalimantan - Hutagalung, Rio Martin Luter (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
PLTS is one of the renewable energy solutions that utilizes solar radiation as the main source of its generation, so it is considered environmentally friendly and has great potential in areas with high sunlight intensity. The research methods used include collecting solar radiation data, PLTS system design, and performance simulation and testing using HOMER Pro software. This research was conducted at the Ministry of Politics, Law and Human Rights Building in the Nusantara Capital development area in Penajam Paser Utara Regency, East Kalimantan. The tool used to help solve this research problem uses software, namely HOMER Pro. Based on the data obtained, the estimated load consumed in these 4 buildings is 4,222 kWh/day. The PLTS is planned to be built with a capacity of 550 Wp with a total of 376 units, while the inverter capacity is 15,000 Watts with 8 units and 11,000 Watts with 8 units. Based on the results of manual calculations and using HOMER Pro software, the payback period value can be obtained of around 8 to 9 years. and this PLTS will be planned to operate for 25 years.